2013
DOI: 10.1371/journal.pone.0059196
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to a Polychlorinated Biphenyl (PCB) Congener Influences Fixation Duration on Biological Motion at 4-Months-Old: A Preliminary Study

Abstract: Adverse effects of prenatal exposure to polychlorinated biphenyl (PCB) congeners on postnatal brain development have been reported in a number of previous studies. However, few studies have examined the effects of prenatal PCB exposure on early social development. The present study sought to increase understanding of the neurotoxicity of PCBs by examining the relationship between PCB congener concentrations in umbilical cord blood and fixation patterns when observing upright and inverted biological motion (BM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 66 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…Acute and chronic exposure to polychlorinated biphenyls (PCBs) may induce neurotoxicity resulting in morphological changes of neurons, developmental defects of the nervous system, behavioral changes, and learning deficits (Winneke, 2011; Doi et al, 2013; Selvakumar et al, 2013; Lesiak et al, 2014). The blood–brain barrier (BBB) is a highly specialized structural and functional barrier separating the microenvironment of the central nervous system (CNS) from the peripheral circulation by restricting paracellular movement of ions and solutes across the brain endothelium (Dodelet-Devillers et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Acute and chronic exposure to polychlorinated biphenyls (PCBs) may induce neurotoxicity resulting in morphological changes of neurons, developmental defects of the nervous system, behavioral changes, and learning deficits (Winneke, 2011; Doi et al, 2013; Selvakumar et al, 2013; Lesiak et al, 2014). The blood–brain barrier (BBB) is a highly specialized structural and functional barrier separating the microenvironment of the central nervous system (CNS) from the peripheral circulation by restricting paracellular movement of ions and solutes across the brain endothelium (Dodelet-Devillers et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“… 29 CB-118 PCB Brucker-Davis et al [ 108 ]: negative impact on neurocognitive development, negatively correlated on motor and expressive language in children. Doi et al [ 109 ]: four-month-olds children with a low-level of prenatal exposure exhibits a preference for the upright biological motion, impairs the development functioning and brain development. 30 CB-126 Planar PCB Cauli et al [ 110 ]: impairs motor coordination at 2 months in males but not in female rats, reduces locomotor activity in females.…”
Section: Resultsmentioning
confidence: 99%
“…As one of the environmental factors for the liability to ASD, the possible involvement of dioxin and/or dioxin-like environmental chemicals was investigated. Although many environmental chemicals affect neurodevelopment in humans, we focused on dioxin and dioxin-like chemicals because we have shown that higher levels of dioxin-like PCBs in the cord blood appear as a manifestation of ASD-like behaviors in 4-month-old infants (40), and also because maternal exposure to such environmental chemicals possibly disrupts fetal gonadal hormone balances, which could lead to EMB (12, 13). The current study investigated the effects of AhR -related gene polymorphisms on ASD susceptibility and/or severity to determine the relationship between possible vulnerability to dioxin and dioxin-like PCBs and ASD susceptibility and/or severity because dioxin and dioxin-like PCBs at low levels have spread almost uniformly throughout the country.…”
Section: Discussionmentioning
confidence: 99%